Impact of donor age on short-term outcomes after pediatric split liver transplantation - Xu, Min; Dong, Chong; Sun, Chao; Wang, Kai; Zhang, Wei; Qin, Hong; Han, Chao; Yang, Yang; Zhang, Fubo; Wang, Zhen; Zheng, Weiping; Wei, Xinzhe; et al. (Frontiers in Pediatrics, 2023)
Background Donor shortage is an important limitation of liver transplantation (LT). Split liver transplantation (SLT) may increase the sources of donors and reduce the problem of organ shortage. However, there are no standard criteria of the selection of SLT donor, especially regarding the donor age. Methods We retrospectively analyzed the clinical data of children who received initial SLT between January 2015 and December 2021. Based on the age of donors, the patients were divided into groups A (1–10 years old; n = 26), B (10–45 years old; n = 87), and C (45–55 years old; n = 27). The short-term (<1 year after SLT) outcomes of the recipients were analyzed. Results A total of 140 patients received SLT from 122 donors. The 1-, 3- and 12-month patient survival rates in group A were 100.0%, and the graft survival rates were 92.3%. The 1-, 3- and 12-month survival rates of patient and graft in group B were 97.7%, 96.6%, and 95.0%, respectively, and in group C were 85.2%, 85.2%, and 81.1%, respectively. The patient survival rate was significantly lower in group C than in groups A and B (p = 0.0082). There was no significant difference in graft survival between the three groups (p = 0.0545). Conclusions Similar results were obtained for pediatric SLT with donors <10 years old and 10–45 years old. Pediatric SLT can be performed with older donors (45–55 years) after strict donor selection and selection of appropriate recipients.